PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN APLIKASI ARTICULATE STORYLINE PADA MATA PELAJARAN INFORMATIKA TENTANG ANALISIS DATA UNTUK SISWA KELAS VIII DI SMPN 1 NGUNUT - Rafindra Khoirur Riza; Abdul Haris Indra Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a website-based interactive learning media using Articulate Storyline for the Data Analysis topic in Informatics for Grade VIII-A students at SMPN 1 Ngunut and to determine its feasibility based on evaluations by media experts, subject matter experts, and student responses. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The resulting product is a website-based learning media that can be accessed through computers and smartphones without requiring additional application installation. The media includes user instructions, learning objectives, learning materials, instructional videos, practice exercises, interactive evaluations, and the developer profile. Data were collected using questionnaires and analyzed through descriptive quantitative analysis based on feasibility percentages. The results showed that the first media expert validation obtained a score of 67.5%, requiring revisions, while the second validation increased to 94%, categorized as highly feasible. The material expert validation achieved 96%, also categorized as highly feasible. Small-group testing involving six students obtained 84.17%, while large-group testing involving thirty students reached 90%, both categorized as highly feasible. Based on these findings, the website-based interactive learning media developed using Articulate Storyline is highly feasible as a supporting learning medium for the Data Analysis topic in Informatics because it provides an interactive, engaging, and accessible learning experience while enhancing students' understanding and learning motivation.